Endoscopic Resection for Small Rectal Neuroendocrine Tumors: Comparison of Endoscopic Submucosal Resection with Band Ligation and Endoscopic Submucosal Dissection. (25th July 2016) - Bang, Byoung Wook; Park, Jin Seok; Kim, Hyung Kil; Shin, Yong Woon; Kwon, Kye Sook; Kim, Joon Mee
Abstract : Background and Aims . There is no consensus so far regarding the optimal endoscopic method for treatment of small rectal neuroendocrine tumor (NET). The aim of this study was to compare treatment efficacy, safety, and procedure time between endoscopic submucosal resection with band ligation (ESMR-L) and endoscopic submucosal dissection (ESD). Methods . We conducted a prospective study of patients who visited Inha University Hospital for endoscopic resection of rectal NET (≦10 mm). Pathological complete resection rate, procedure time, and complications were evaluated. Results . A total of 77 patients were treated by ESMR-L (n = 53 ) or ESD (n = 2 4 ). En bloc resection was achieved in all patients. A significantly higher pathological complete resection rate was observed in the ESMR-L group (53/53, 100%) than in the ESD group (13/24, 54.2%) (P = 0.000 ). The procedure time of ESD (17 . 9 ± 9 . 1 min) was significantly longer compared to that of ESMR-L (5 . 3 ± 2 . 8 min) (P = 0.000 ). Conclusions . Considering the clinical efficacy, technical difficulty, and procedure time, the ESMR-L method should be considered as the first-line therapy for the small rectal NET (≤10 mm). ESD should be left as a second-line treatment for the fibrotic lesion which could not be removed using the ESMR-L method.